Chitosan films containing TiO2 nanoparticles modified with tungstophosphoric acid for the photobleaching of malachite green in solid-gas interfaces upon different wavelengths - Rengifo-Herrera J.A. (2018)
Authors thank Lilian Osiglio and Mariela Theiller for their experimental collaboration. Financial support from CONICET (Project PIP 0449) and Universidad Nacional de La Plata (Project X-773 and X-732) is also acknowledged. J.A. Rengifo-Herrera thanks Universidad Nacional de San Agustin and CONCYTEC from Peru for the financial support of E. Mendoza-Portillo’s scientific stage.